The effect of using Ginger (Zingiber officinale) or parsley seeds (petroselinum sativum) on some of physiologically traits of black: Mudhaffar N.R.Al-Saigh and Mohammed M. Dakheel - Dakheel, Mohammed M. (The Iraqi Journal of Veterinary Medicine, 2012)
The study was aimed to know the effect of adding 3% of grind zingiber officinale or 8% ofpetroselinum sativum seeds in the concentrate diet (400g/head/ daily) of the Black Iraqi Does (19does) in some physiological traits. Nineteen healthy weak-medium does were divided into threegroups, the first group of 6 does fed concentrate diet containing zingiber, while in the secondgroup (6) does were fed on a diet containing 8% grind petroselinum sativum seeds, however, theother does kept as control group and fed the concentrate diet free of the herbal medical additivesduring mid December 2009 up to end of May 2010. The results revealed that group, The first andsecond groups were highly significant (p>0.05) in their Hb and PCV during the late months ofthe study, also both feed additives caused significant (p>0.05) increase in WBCs, lymphocyte andmonocytes ratio, while they caused significant decrease in neutrophils compared with the controlgroup. The total serum protein and albumin of Animals of both groups fed herbal medicine werehighly significant (p>0.05) in comparing with the control group. While the globulin level was notaffected, also blood sugar of both groups fed zingiber or petroselinum seeds showed significant(p> 0.05) lower levels during the late months of the study.